PENGEMBANGAN MEDIA BUSY BOOK UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA TEMA 5 CUACA DI KELAS III SD - Depiana Sembiring (CV. ADIBA AISHA AMIRA, 2024)
The problems found in grade III elementary school are that teachers only use the method of contemplation and teaching so that there are some students who find it difficult to understand the material explained by the teacher so that students only fantasize in grasping the material taught, the lack of learning media that is able to present concrete material on the weather material only using printed books so that some students in the class were sleepy. This research uses a development model or in English it is called Research and Development (R&D). The purpose of this study is to find out the Development of Busy Media to Improve Student Learning Outcomes on Theme 5 Weather in Grade 3 Elementary School. Development research is a research method used to produce a certain product, and to test the effectiveness of the product (Sugiono, 2015:407). Based on the results of research and development that has been carried out by the research, it can be concluded that research and development use the stages of the ADDIE model, but this research is only carried out until the product development tap, namely the Bussy Book learning media in the learning of the 5 weather theme. Based on the feasibility of the media from the input of experts, namely lecturers and teachers, media experts are lecturers. And the data from the validation results from lecturer material experts reached 94%. Media experts 98% and learning experts 93%. From the calculation above, 94%, 93% and 98% are categorized as Bussy Book learning media that is very suitable for use. Therefore, the development of Bussy Book media on the theme of 5 weather in grade 3 elementary school developed by the researcher is declared very feasible to be used as a medium in the learning process.